2007
DOI: 10.1002/polb.21194
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the polyelectrolyte and antipolyelectrolyte effects of poly(N‐vinylimidazole‐co‐sodium styrenesulfonate) hydrogels

Abstract: Hydrogels of N‐vinylimidazole (VI) and sodium styrenesulfonate (SSS) were synthesized in aqueous solution by radical crosslinking copolymerization with N,N′‐methylene‐bis(acrylamide) as crosslinker. Swelling in several saline solutions was measured for hydrogel samples synthesized with different comonomer concentrations (CT = 10, 25, or 40%) and with SSS mole fractions covering a broad range (fSSS = 0–0.7), while the crosslinker ratio was 2 wt % in all cases. The degree of swelling in aqueous solution with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The affine model and gaussian chains were considered for P el . 22,24,31 Equation (5), with 16 v ¼ 0.496 þ 0.308v 2 , affords the m e (S) values plotted in Figure 5 for PVI swollen in deionized water.…”
Section: Effective Crosslinking Densitymentioning
confidence: 93%
See 2 more Smart Citations
“…The affine model and gaussian chains were considered for P el . 22,24,31 Equation (5), with 16 v ¼ 0.496 þ 0.308v 2 , affords the m e (S) values plotted in Figure 5 for PVI swollen in deionized water.…”
Section: Effective Crosslinking Densitymentioning
confidence: 93%
“…To obtain v in acid solutions, the protonation of the imidazole rings and the subsequent ionic contribution to the osmotic swelling pressure must be considered 22,24 and thus, it results that v ¼ (0.547 AE 0.008) þ (0.01 AE 0.07)v 2 , for PVI swollen in HCl aqueous solution with pH i ¼ 4, which corresponds to a degree of protonation within the range 0.0121 AE 0.0005.…”
Section: Solvent Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency of polyelectrolyte complexes and polyampholyte systems to swell with water upon addition of salt has been called the "antipolyelectrolyte effect" (Valencia and Pierola 2007;Dogu et al 2009;. Because this effect appears to be consistent with the behaviour of the hemicellulose-based PECs just described, some background will be given here.…”
Section: Antipolyelectrolyte Effectmentioning
confidence: 99%
“…As an underlying explanation for the effect, it has been shown that the addition of salt tends to weaken the electrostatic interactions within a PEC (Dragan and Cristea 2001). Increased absorbency with increasing salinity of aqueous solutions has been observed in several cases in which oppositely charged polyelectrolytes were employed in the preparation of cellulose-or hemicellulose-based hydrogels (Paula et al 2002;Feng and Pelton 2007;Valencia and Pierola 2007;Shang et al 2008;Salam et al 2011a,b;Gawel et al 2012). Such weakening of the pair-wise associations of ionic groups on the polymer chains allows a partial reversal of the process…”
Section: Antipolyelectrolyte Effectmentioning
confidence: 99%